The Malaysian Islamic Party (PAS) in 14th General Elections (GE-14) in Sabah: a Study on Voting Pattern, Campaign Approaches and Society’s Perception - Mohamad Shaukhi Mohd Radzi; Syahruddin Awang Ahmad; Nordin Sakke (2018)
The study uses participatory observation and secondary data analysis on campaign approaches and the pattern of voting back to the Islamic Party of Malaysia (PAS) in the past 14th General Election (GE), witnessing the fierce competition between Sabah PAS and other political parties in the state this is. A moderate level of support and the ability to attract Sabah people to cast a significant vote for PAS is a winding-up of PAS Sabah in realizing the 'eldest child' for the GE. A relatively incomplete support pattern also shows that Muslim and non-Muslim communities in Sabah seems to be well guided and rectified their perceptions of the true ability of Islam as the essential foundation of life. The clarity of the aspirations of 'prosperous ideas' as a manifesto of PAS is good for all multiracial and religion in the Sabah, but not until PAS Sabah get its mandate to govern this state even PAS itself is known for its long-standing Party in this country, Only then the goodness brought by Islam through PAS can be realized. Thus, the approach of the Islamic-based campaign and the ‘muwajahah silmiyyah’ is crucial for enhancing its methods and channels in order to preach the message regarding Islamic values for all the people in the state. It needs to be streamlined specifically for PAS Sabah to inculcate confidence in multiracial society in the state in line with its struggle. The advantages of PAS are the vast experience in controlling ways of campaigning like Group Lecture approach and of course the Facebook app through the Virtual Campaign. This aspect of being emphasized by incorporating economic and social development ideas in Sabah should be able to reinforce the party's campaign strategy and tactics to succeed in gaining greater votes in the coming 15th General Election.